The impacts of energy insecurity on household welfare in Cambodia: Empirical evidence and policy implications - Han Phoumin; Fukunari Kimura (Asian Development Bank Institute (ADBI), 2019)
This study investigates the impacts of energy insecurity on household welfare in Cambodia. The notion of energy insecurity is not well understood in the literature or in local contexts. This study defines household energy insecurity as the status quo derived from the interplay of inadequate and insufficient energy consumption that prevents households from meeting their basic energy needs. The notion of energy insecurity can only be understood well through an investigation in the local context, as it varies from place to place. Households facing insufficient energy consumption may forgo many other opportunities. Having defined energy security in the Cambodian context, the study employs the Cambodia Socio-Economic Survey Data (2015) to investigate the impacts of household energy insecurity. The study confirms that energy insecurity has an enormous negative impact on households' welfare, with a further negative impact on children's human capital formation. The findings lead to policy implications for improving household energy security and thus influencing economic, social, and environmental development.
Keywords: Q48; C39; I39; 330; energy insecurity; schooling; welfare